Conocimiento de los pacientes sobre el cuidado de prótesis fija/removible y creación de un manual destinado a la promoción de higiene y cuidado protésico - Gonzabay Campos, Diana Valeria (2016)
In the literature review we can find that the use of dental prosthesis is very common, however the knowledge of care in patients using them is not as familiar. The project conducted, identified prior knowledge and habits that bears the respondent regarding the care and maintenance of prostheses. The manual was presented on the website, giving new instructions and being evaluated at the end. The aim of the study was to identify the current awareness of the partial and total edentulous patients on prosthetic care, creating an educational proposal in colloquial language, less technical, facilitating understatement for patients. Selfcare, sanitation, and maintenance of dental prostheses are the main topics in the manual. The research was conducted within the University of the Americas to 50 patients with dental prosthesis, occupying forms. Data analysis, knowledge of maintenance, and cleaning of dental prostheses was not the most optimal by patients. Foreknowledge was redirected, the evaluation was responded satisfactorily, following the instructions given by the manuals. The project was successful inasmuch as learning.